2015
DOI: 10.5152/ucd.2015.2993
|View full text |Cite
|
Sign up to set email alerts
|

The effect of laparoscopic sleeve gastrectomy on morbid obesity and obesity-related comorbidities: A cohort study

Abstract: Objective: Bariatric surgery with multidisciplinary management is a more effective method to treat morbid obesity and obesity-related comorbidities compared with nonsurgical treatments. Laparoscopic sleeve gastrectomy (LSG) was initially performed as the first stage of biliopancreatic diversion with duodenal switch in the super-obese population. In the past few years, however, LSG has been performed as a definitive procedure because of its promising early and midterm results. The aim of this study is to evalua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…This finding is concordant with the study by Ochner et al (27) reporting that the effect of preoperative BMI was apparent, heavier individuals showed lower percentages of initial and excess weight loss, and that this effect was particularly apparent after the initial rapid weight loss phase during the first year, when patients with BMI <50 continued losing weight, while patients with BMI ≥50 regained significant weight. Another cohort study reported significant weight loss and improvement of T2DM, hypertension and dyslipidemia after LSG in 78 patients whose BMI was less than 50 (28).…”
Section: Discussionmentioning
confidence: 96%
“…This finding is concordant with the study by Ochner et al (27) reporting that the effect of preoperative BMI was apparent, heavier individuals showed lower percentages of initial and excess weight loss, and that this effect was particularly apparent after the initial rapid weight loss phase during the first year, when patients with BMI <50 continued losing weight, while patients with BMI ≥50 regained significant weight. Another cohort study reported significant weight loss and improvement of T2DM, hypertension and dyslipidemia after LSG in 78 patients whose BMI was less than 50 (28).…”
Section: Discussionmentioning
confidence: 96%
“…The long-term effects of diet, drug, and endoscopic solutions seem to be limited. Surgery is the most effective treatment in the appropriate indication [ 7 ]. For this reason, the number of surgeries is increasing every year and LSG has become the most performed surgery [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, although there are publications on the fact that robotic surgery can help in coping with mirror image, there is a shortage of data on this subject [ 15 ]. In addition, left-handed surgeons are thought to be advantageous over right-handed surgeons in patients with SIT [ 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…As such, it is one of the most commonly performed bariatric procedures. 9 SIT is merely one of many challenges surgeons encounter in bariatric surgery. 10 …”
Section: Discussionmentioning
confidence: 99%